Influence of gadolinium doping on structural properties of carbon nanotubes - Abaszade, R.G.; Babanli, M.B.; Kotsyubynsky, V.O.; Mammadov, A.G.; Gür, E.; Kapush О.А.; Stetsenko, M.O.; Zapukhlyak, R.I. (Physics and Chemistry of Solid State, 2023)
The paper presents an analysis of SEM, EDX, Raman scattering, and FTIR of Gadolinium-doped multi-walled carbon nanotubes obtained by hydrothermal method. The morphological characteristics of the materials were studied and their compositions were analyzed. Hydrothermal doping of MWCNs with Gd causes the formation of 3D network architecture and sharply increases the content of oxygen surface functionality. An unidentified intense broad peak for Gd-doped material at 2940 cm-1 was observed. The defect state of Gd-doped MWCNTs was studied by Raman spectroscopy.